Draft Annual Plan 1986-87 Government of Gujarat - Planning Commission (Planning Commission, 1985)
With, the commissioning of one unit of 110 MW of Ahmedabad Electricity Co., and the fifth unit of 210 MW of Ukai Thermal Power Project in 1984-85, the total installed capacity in the State available for power generation including the share of Tarapur Nuclear Power Station and Korba Super Thermal Power Station was 3383 MW at the end of 1984-85.
Government of Gujarat, General Administration Department (Planning)